(untitled) (Research, Society and Development, 2024)
Given the increase in demand and commercialization of purified water in electronic fountains in Assú, this article aims to present research results of the profile analysis of purified water consumers in electronic fountain-type establishments in Assú City, RN State, Brazil. Social research was carried out (carried out with people), an exploratory survey with qualitative and quantitative analysis using a questionnaire to identify a set of characteristics that define habits and preferred behavior related to a given product. To this end, 16 questions were developed about the routine of purchasing this water and then randomly applied to an audience totaling 100 individuals who claim to be consumers of this product. Regarding the results, it was observed that the main reason for consuming this water was the low cost, the best way to sanitize the bottle, and the use of soap was verified, and the majority are unaware that there is supervision in this establishment. Many consumers have difficulty following the hygiene and handling instructions set out by the establishment, as well as the electronic fountain itself does not facilitate or encourage the practice of this hygiene, such as, for example, providing 70 ºGL alcohol. Therefore, consumers must pay extra attention throughout the purchasing process and drinking water, especially in electronic fountain-type establishments, so as not to compromise the product in terms of contamination conditions and consequently experience any health problems.